The Effectiveness of Bank Indonesia's SME Development Strategies, Policies, and Support in Financial Technology - Cakra Wirabuana; Betty Purwandari; Imairi Eitiveni; Erisva Hakiki Purwaningsih (Faculty of Computer Science Universitas Indonesia, 2025)
This study aims to assess the effectiveness of strategies, policies, and support offered by Bank Indonesia for the growth of Small and Medium Enterprises (SMEs) in the Financial Technology (FinTech) sector. Using qualitative methods, thematic analysis, and frequency analysis, this study highlights the existing gaps in research on institutional support for SMEs during the digital era, especially within the Indonesian framework. A significant contribution of this research is the detailed exploration of SMEs' perspectives on the support they receive, focusing on areas such as infrastructure, digital literacy, and regulatory frameworks. Findings show that SMEs are generally positive about Bank Indonesia's initiatives, despite challenges in technical, administrative, and networking aspects. In addition, this research proposes actionable recommendations for Bank Indonesia and other relevant bodies to improve FinTech infrastructure, increase awareness and education, and revise regulations to better facilitate SME development. In addition, this research lays the groundwork for future longitudinal and comparative analyses to measure the long-term impact of Bank Indonesia's policies and to create predictive models that can pinpoint important elements that influence the use and success of digital payment solutions among SMEs. In addition to offering policy insights for Indonesia, this research also contributes to the broader global context by understanding the role of institutional support in advancing SMEs in the FinTech industry.